Biologic Responses to House Dust Mite Exposure in the Environmental Exposure Unit - Hossenbaccus, Lubnaa; Linton, Sophia; Thiele, Jenny; Steacy, Lisa; Walker, Terry; Malone, Crystal; Ellis, Anne K. (Frontiers in Allergy, 2022)
Introduction: Allergic rhinitis (AR) is an inflammatory disease of the nasal mucosa that can be modeled using Controlled Allergen Exposure Facilities (CACF). Recently, we clinically validated the house dust mite (HDM) Environmental Exposure Unit (EEU) facility. In the current study, we aimed to assess biological responses in the blood following HDM exposure in the HDM-EEU. Methods: Fifty-five participants passed a screening visit, where they provided consent and completed a skin prick test (SPT), then attended a modest or higher HDM exposure session. Baseline and post-exposure blood samples were collected. Complete blood counts with differentials were measured, and isolated serum was used to determine Dermatophagoides farinae- and Dermatophagoides pteronyssinus-specific IgE (sIgE) and cytokine concentrations (IL-4, IL-5, IL-6, IL-10, IL-13, TNF-α). Results: HDM-allergic participants had significantly greater SPT wheal sizes than healthy controls. sIgE concentrations were significantly greater in allergic participants, with a strong correlation between Dermatophagoides farinae and Dermatophagoides pteronyssinus. Serum eosinophil counts were significantly decreased post-exposure for allergic participants. White blood cell, neutrophil, and lymphocyte counts were significantly increased for both allergic and non-allergic participants post-exposure. Serum IL-13 concentrations were significantly reduced post-exposure in allergics while TNF-α was significantly reduced in non-allergics. Conclusion: The HDM-EEU is a useful model for investigating biologic mechanisms of HDM-induced AR. Allergic participants produced measurable biological changes compared to healthy controls following allergen exposure, specifically with serum expression of eosinophils and related markers, namely IL-5, which promotes the proliferation and differentiation of eosinophils, and IL-13, a cytokine released by eosinophils. The exact mechanisms at play require further investigation.